2015
DOI: 10.1097/ta.0000000000000796
|View full text |Cite
|
Sign up to set email alerts
|

A prospective analysis of urinary tract infections among elderly trauma patients

Abstract: Introduction Catheter-associated urinary tract infections (CAUTI) have been deemed “reasonably preventable” by the Centers for Medicare and Medicaid (CMS) thereby eliminating reimbursement. Elderly trauma patients, however, are at high risk for developing urinary tract infections (UTI) given their extensive comorbidities, immobilization, and environmental changes in the urine which provide the ideal environment for bacterial overgrowth. Whether these patients develop CAUTI as a complication of their hospitaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 9 publications
0
14
0
1
Order By: Relevance
“…As part of an observational trial of 129 elderly patients (Ն65 years old) admitted to the hospital following accidental injury, most of whom were catheterized on admission, urine sediments were examined to determine whether undiagnosed UTI and ASB potentially contributed as causes of the trauma suffered. We previously reported that 25% of the cases examined by urinalysis and urine culture showed evidence of bacteriuria on admission (24), suggesting that the rationale to declare CAUTI a preventable disease in the nosocomial environment is confounded by preexisting bacteriuria in elderly patients (8). Here, we analyzed the metaproteome of 100 urinary sediment samples from all patients with evidence of bacteriuria and 12 patients with negative UC test results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As part of an observational trial of 129 elderly patients (Ն65 years old) admitted to the hospital following accidental injury, most of whom were catheterized on admission, urine sediments were examined to determine whether undiagnosed UTI and ASB potentially contributed as causes of the trauma suffered. We previously reported that 25% of the cases examined by urinalysis and urine culture showed evidence of bacteriuria on admission (24), suggesting that the rationale to declare CAUTI a preventable disease in the nosocomial environment is confounded by preexisting bacteriuria in elderly patients (8). Here, we analyzed the metaproteome of 100 urinary sediment samples from all patients with evidence of bacteriuria and 12 patients with negative UC test results.…”
Section: Resultsmentioning
confidence: 99%
“…The Internal Review Boards of the Mayo Clinic and the J. Craig Venter Institute (JCVI) approved the human subject protocol and the consent forms in application no. 12-010185 (24). All patients had a blunt mechanism of injury, with falls from a standing height in 76% of the cases.…”
Section: Methodsmentioning
confidence: 99%
“…As long-term catheters play a fundamental role in contracting UTI in elderly patients, it should only be reserved for serious urinary retention conditions like the neurogenic bladder, etc 20 . People with poor health status should be given more attention, and sudden instability of the patient must be evaluated cautiously and should be treated promptly to prevent any unfortunate consequences [19][20][21][22][23][24] . Health professionals should be trained up adequately to take care of these conditions ensuring the delivery of high-quality healthcare for elderly patients suffering from UTI.…”
Section: Resultsmentioning
confidence: 99%
“…Conditions like the kidney stone, diverticula and stricture should be investigated properly to avoid further complication 21,22 . For diabetic patients, blood glucose will regularly be monitored, and the appropriate drug should be given as blood sugar increases the risk of relapse and reinfection 23 . Patients on immunosuppressive agents also demand particular attention in this regard 23,24 .…”
Section: Preventing Uti In Hospitals and Aged Care Facilitiesmentioning
confidence: 99%
“…Tüm yaşlarda ÜSE etkenleri arasında en sık karşılaşılanlar E. coli başta olmak üzere Klebsiella spp., Proteus mirabilis, Pseudomonas spp., diğer Gram-olumsuz bakteriler, Staphylococcus saphrophyticus ve enterokoklardır [12] . İleri yaş travma hastalarında gelişen ÜSE'lerin değerlendirildiği prospektif bir çalışmada E. coli ve enterokoklar en sık saptanan etkenler olarak bildirilmiştir [13] . Çalışmamızda ise en sık karşılaşılan etkenler E. coli, K. pneumoniae ve enterokoklardır.…”
Section: Discussionunclassified